The effectiveness of the SEPTIA model integrating Taneyan Lanjhang local values on elementary students’ social-cultural literacy - Nanda Septiana; Wahono Widodo; Ganes Gunansyah; Gül Erkol Bayram (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to evaluate the effectiveness of the SEPTIA model (Solving Education through Problem, Tradition, and Indigenous Approach) in enhancing fourth-grade students’ socio-cultural literacy in elementary natural and social science studies (IPAS). The model integrates Problem-Based Learning (PBL) with the local cultural values of Taneyan Lanjhang to develop four dimensions of socio-cultural literacy: intellectual (analysis of social issues), social (empathy and tolerance), cultural (appreciation of local values), and collaborative (cooperative problem-solving skills). A quasi-experimental pretest–posttest control-group design was implemented, involving 50 fourth-grade students from two elementary schools in Pamekasan (25 in the experimental group and 25 in the control group). Data were collected using a validated socio-cultural literacy test and structured observation sheets, and were analyzed through paired-sample t-tests, independent-sample t-tests, and Cohen’s d effect size. The results indicate that the experimental group demonstrated a statistically significant improvement in socio-cultural literacy scores compared to both their pre-test performance and the control group (p < .001). The mean score increased from 59.39 to 77.03 in the experimental group, whereas the control group exhibited a comparatively smaller gain. The effect size was large (d = 1.72), indicating a substantial impact of the SEPTIA model. All four dimensions of socio-cultural literacy improved, with the most pronounced gains observed in the social and cultural dimensions. These findings suggest that integrating local cultural values into a PBL framework is an effective pedagogical strategy for enhancing students’ socio-cultural literacy. This study advances culturally responsive and context-based instructional models in elementary education, particularly by fostering social and cultural competencies alongside cognitive development.